Thermophysical Parameter Measurements and Stress Analysis of LaFeO3/8YSZ Double-Layer Coatings - CAO Boran, TAN Zheng'ao, HE Yongxiang, HU Yanhao, XU Yusheng, GUO Hong, DAI Cuiying, ZHOU Zhe, WANG Jie, HUANG Wenzhi, LI Sha, ZUO Jinglu, MAO Weiguo (Cailiao Baohu)
The thermal barrier stealth integrated coating material prepared by atmospheric plasma spraying process has important application prospects in the hot end components of aircraft engines.For studying the optimization of atmospheric plasma spraying process parameters for LaFeO3/8YSZ composite coating， a pure LaFeO3 coating was first prepared， and high-temperature characterization of the thermal and physical parameters of the coating was completed at 1 150 ℃.A finite element model of LaFeO3/8YSZ composite coating was established，and the influence of preparation temperature and coating thickness ratio on residual stress of the sample was analyzed in detail.Results showed that as the preparation temperature increased， the in-plane compressive stress of LaFeO3 and 8YSZ coatings gradually increased.The surface internal stress of LaFeO3 coating changed from -96 MPa at 150 ℃to -152 MPa at 250 ℃， and similarly， the surface internal stress of 8YSZ coating increased from -48 MPa to -86 MPa.Besides，the compressive stress state was beneficial for extending the service life of coatings in high-temperature service environments.Due to the thermal expansion coefficient of LaFeO3 being close to that of 8YSZ， the change in the thickness ratio of LaFeO3/8YSZ had little effect on the residual stress distribution of the double-layer coatings at a given total coating thickness of 1.0 mm.